Work Life Balance and Employees’ Career Success - Manandhar, Sushma (PYC Nepal Journal of Management, 2011)
The paper aims to examine the work-life balance and employees’ career success in the Nepalese television and hospital industries. The impacts of individual, organizational and social variables were studied in different dimensions to obtain more complete and accurate picture of variables related to the work life balance and its impact on the employees’ career success. A structured questionnaire survey of 150 employees was conducted in the two industries located in the Kathmandu Valley. The descriptive research design, reliability analysis (Cronbach’s alpha), correlation and regression analyses were used to observe and test the hypotheses. The social supports from family and social supports from work place have significant positive effect on work life balance both in television and hospital sectors. The same result was found in case of job satisfaction and family satisfaction with work life balance. The significant positive effects of job satisfaction and family satisfaction were also found on employees’ career success. The work life balance was found with significantly positive effect on job satisfaction. Finally, the study showed the significant positive effect of work life balance on employees’ career success in both the sectors.